Non-strongly isospectral spherical space forms - Lauret, Emilio Agustin (2016)
In this paper we describe recent results on explicit construction of lens spaces that are not strongly isospectral, yet they are isospectral on p-forms for every p. Such examples cannot be obtained by the Sunada method. We also discuss related results, emphasizing on significant classical work of Ikeda on isospectral lens spaces, via a thorough study of the associated generating functions.